NORMATIVE-METHODICAL BASIS OF NORMATIVE MONETARY ASSESSMENT OF LANDS OF POPULATED AREAS - Titova, S.; Demchenko, D. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2018)
On the basis of information on the implementation of the normative monetary valuation of settlements, analysis and structuring of the information given in the normative-legal framework are made, the main documents regulating the execution of the indicated assessment are considered in the article.
Keywords: normative estimation, monetary estimation, settlements, normative-legal base, legislation